Determinan Perilaku Manajemen Keuangan pada UMKM Bengkel Las di Kecamatan Karangrejo Tulungagung - Lailatul Hamidah; Amalia Nuril Hidayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of Financial Knowledge, Financial Attitudes, Education Level and Financial Income on Financial Management Behavior in micro, small and medium-sized entrepreneurs in welding workshops in Karangrejo Tulungagung District. This research is a quantitative research with the research population, namely micro, small and medium enterprises in welding workshops located in Tulungagung District. Sampling in this research used Field Research techniques. Data collection was carried out by distributing questionnaires to find actual data for 31 respondents. The analysis techniques used are statistical analysis, hypothesis testing and data quality testing. Test the validity of each questionnaire item using the product moment correlation method between the score of each questionnaire item and the total score (the sum of each questionnaire score). Then carry out a reliability test using Cronbach's alpha. The results of this research show that Financial Knowledge, Financial Attitudes, Education Level and Financial Income have a significant and positive influence on financial management behavior.